The Correlation Between the Duration of Playing Online game and the Game Type with the Depression Level of Young Adult Visitor in Kingdom Game Centre Surakarta - Reinaldo, Pieter; Syamsulhadi, Much.; Yuliadi, Istar (Nexus Kedokteran Klinik, 2015)
Introduction: Online game is quite popular for an entertainment source in all over the world, according Indonesia. Online games has magical attraction that makes people eager to play it, such as three dimension graphic (3D), social and competitive aspect, as well as the play that runs like in real time. Several research reveal that playing online game too much can lead to a bad effect for the mental health of the player. This research has the purpose to find out whether there is a correlation between the duration of playing online game and the game type with the depression level of young adult visitor in Kingdom Game Centre Surakarta Methods: The kind of this research is analytical observational research with cross sectional approach. The population is the young adult visitor of Kingdom game centre in Surakarta. During March 2015, by using fixed exposure technique sampling, the researcher took sample of 56 repondents who fulfill the criterion. Duration of playing and type of online game is measured by using questionnaire, depression level is measured by using Beck Depression Inventory (BDI). The data is analysed by using double linear regression technique. Result: The duration time of playing online games has comparable significant correlation with the playerâs depression level (p = 0,018). Type of game has significant correlation with the playerâs depression level (p = 0,049), in which the player of MMORPG game has higher depression score compared with the player of MMORTS or MMOFPS. With the closeness of the relationship between these three variables is approximately (0,508). The accuracy of regression model 0.215 showed that 21.5% depression that occurred at the sample is due to the duration and type of game Conclusions: The longer the duration of playing online game then the depression will be heavier. MMORPG player will have heavier depression level compared with the player of other type of games. Keywords: Duration of Playing Online Game, Type of Online Game, Depression Level